The career transition between basketball champions in the amateurism phase - Rubio, Katia (Advances in Social Sciences Research Journal, 2015)
The sports professionalism in times of amateurism was once regarded as much immoral as the practice of using doping substances in the contemporary sport. Being amateur was a determining condition for the athlete to be able to enter the Olympic arena and to validate their medals and records. This life style, though, had a high cost for those unable to subsist from the sport practice, but instead dependent on the remunerated professional activity to survive. The objective of this essay was to analyze how the athlete from amateurism times used to manage the athletic career and experienced the transition for the post-athlete life respectively. Collaborating with this survey there are 10 post-athletes, former basketball players who shared successful experiences of great international repercussion, such as the second world championship (1959 and 1963) and the bronze Olympic medals (1960 and 1964). By means of biographical narratives of Rosa Branca, Antônio Sucar, Wlamir Marques, Amaury Pasos, Menon, Boccardo, Vitor, Carlos Massoni (Mosquito) and Jatyr, it was possible to reunite elements to understand the importance of the historical moment of the sport in terms of the adoption of more provident strategies for the management of the sports career. This enabled the athletes to experience the phases of termination and change of roles with coping resources and, consequently, being free of major problems, even if the absence of formal systems to support the transition hindered the process of resources construction.